Comparing the Effects of Core Stability and Williams Training on Dynamic Balance and Back Pain in Women With Chronic Back Pai - Hamid Zahedi; Raziyeh Kiyani (Sport Sciences and Health Research)
Introduction: This research aimed to compare the effects of the Williams and core stability training on dynamic balance and back pain in women with chronic back pain. Materials and Methods: In total, 45 women with chronic back pain were selected as the available sample and were randomly divided into 3 groups of 15 participants, including core stability, Williams, and control. Before the beginning and the end of the training period, the dynamic balance with the Star Excursion Balance Test (SEBT) and low back pain with Québec Questionnaire was measured. To analyze the obtained data, Analysis of Covariance (ANCOVA) was used in SPSS at P<0.05.Results: The present study findings revealed a significant difference in core stability and Williams training on dynamic balance and improvement in the extent of low back pain in the study participants. There was a significant difference between the training groups in dynamic balance; however, there was no significant difference in the improvement of low back pain between the experimental groups.Conclusion: To improve dynamic balance, a core stability training program is recommended, and Williams’ flexor movements are more appropriate for reducing low back pain.